A not so foreign affair : fascism, sexuality, and the cultural rhetoric of American democracy - Slane, Andrea, 1964- (Duke University Press, 2001)
An examination of how the aesthetics of Nazi Germany have been deployed to help define the place of sexuality in U.S. political and popular culture.